2021
DOI: 10.1002/jmri.27604
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion and Dynamic Contrast‐Enhanced Magnetic Resonance Imaging to Early Detect Tissue Injury and Microcirculation Alteration in Hepatic Injury Induced by Intestinal Ischemia–Reperfusion in a Rat Model

Abstract: Background Intravoxel incoherent motion (IVIM) can provide quantitative information about water diffusion and perfusion that can be used to evaluate hepatic injury, but it has not been studied in hepatic injury induced by intestinal ischemia–reperfusion (IIR). Dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) can provide perfusion data, but it is unclear whether it can provide useful information for assessing hepatic injury induced by IIR. Purpose To examine whether IVIM and DCE‐MRI can detect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…When evaluating hepatic injury induced by intestinal ischemia–reperfusion, Yang et al found that f gradually decreased with the progress of reperfusion, while K trans gradually increased, indicating that the presence of microcirculatory disorder and increased vascular permeability caused by inflammatory cytokines in the liver. Our study found that f was negatively correlated with K trans , which perhaps because of increased capillary permeability in the area of BME and microcirculatory disorder due to cell edema and inflammatory cell aggregation ( 43 ). Some studies have shown that there are differences in aspects of immunology, genetics, and hormone between men and women, such as higher circulating IL-17A and tumor necrosis factor-alpha (TNF-α) levels in men than in women with AS, which may affect the inflammatory pathways leading to bone damage and ultimately influence the progression of the radiographic changes ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 74%
“…When evaluating hepatic injury induced by intestinal ischemia–reperfusion, Yang et al found that f gradually decreased with the progress of reperfusion, while K trans gradually increased, indicating that the presence of microcirculatory disorder and increased vascular permeability caused by inflammatory cytokines in the liver. Our study found that f was negatively correlated with K trans , which perhaps because of increased capillary permeability in the area of BME and microcirculatory disorder due to cell edema and inflammatory cell aggregation ( 43 ). Some studies have shown that there are differences in aspects of immunology, genetics, and hormone between men and women, such as higher circulating IL-17A and tumor necrosis factor-alpha (TNF-α) levels in men than in women with AS, which may affect the inflammatory pathways leading to bone damage and ultimately influence the progression of the radiographic changes ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 74%
“…For the Siemens MR scanner, ADC maps were generated automatically after DWI scans were completed, using b values of 50 and 800 sec/mm 2 . For the GE scanners, DWI images were imported into GE Advanced Workstation (AW 4.6) 23 to obtain ADC maps, with b values of 0 and 1000 or 800 sec/mm 2 . DCE sequences were acquired before and four or five times after contrast agent (Magnevist, Bayer HealthCare Pharmaceuticals Inc., Wayne, USA) injection at a dose of 0.1 mmol/kg of body weight with an injection rate of 1.5–2.0 mL/sec followed by a 20 mL saline flush.…”
Section: Methodsmentioning
confidence: 99%
“…Sheng et al demonstrated that DWI can detect and distinguish microstructural tissue changes during ALPPS and PVL procedures (Sheng et al, 2018 ). DWI has been applied to assess hepatic ischemia and reperfusion injury (Lu et al, 2017 ; Yang et al, 2021 ) and to predict survival after partial hepatectomy (Muhi et al, 2013 ).…”
Section: Clinical and Experimental Partmentioning
confidence: 99%